THEORETICAL FOUNDATIONS OF LEXICAL ECONOMY AND ITS EXPRESSION THROUGH STYLISTIC DEVICES IN ENGLISH AND UZBEK - Abdusamatova Durdonaxon Sodiqjon qizi (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Annotation. This article explores the theoretical foundations of lexical economy and its realization through stylistic devices in English and Uzbek. Lexical economy is understood as the ability of language to convey a maximum amount of information with a minimum number of linguistic units. The study investigates the role of ellipsis, metaphor, metonymy, synecdoche, phraseological units, abbreviations, and conversion as principal mechanisms of semantic compression. The research demonstrates that despite belonging to different typological groups, English and Uzbek share a common tendency toward concise and semantically dense expression. At the same time, the structural realization of lexical economy is determined by the specific grammatical organization of each language. English, as an analytic language, frequently relies on conversion, abbreviation, and syntactic reduction, whereas Uzbek, as an agglutinative language, achieves economy through productive affixation and contextual omission. The findings confirm that stylistic devices perform not only expressive but also cognitive and communicative functions by increasing semantic density and enhancing pragmatic impact.